Facies characterization and sequential evolution of an ancient offshore dunefield in a semi-enclosed sea: Neuquén Basin, Argentina - Veiga, Gonzalo Diego (2017)
This study analyses a 30-m-thick, sand-dominated succession intercalated between offshore mudstones in the Lower Cretaceous record of the Neuquen Basin, Argentina, defining facies associated with unidirectional currents as sand dunes (simple and compound), rippled sand sheets and heterolithic sheets. These facies associations are related to the development of an offshore, forward-accreting dunefield developed as a response to the onset of a tidal-transport system. The reported stratigraphic record results from the combination of the gradual downcurrent decrease of the current speed together with the long-term climbing of the entire system. Maximum amplification of the tidal effect associated with incoming oceanic tides to this epicontinental sea would develop at the time of more efficient connection between the basin and the open ocean. Thus, the onset of the offshore tidal system approximately corresponds to the time of maximum flooding conditions (or immediately after). The short-term evolution of the tidal-transport system is more complex and characterized by the vertical stacking of small-scale cycles defined by the alternation of episodes of construction and destruction of the dunefield. The development of these cycles could be the response to changes in tidal current speed and transport capacity.